Sirtuins and tumor immunity: mechanistic insights, immunotherapy prospects, and therapeutic horizons - Gu, Jinning; Liu, Shanshan; Xiao, Wen; Qu, Wei (Frontiers in Immunology, 2025)
Sirtuins (SIRTs), a family of NAD+-dependent enzymes, exhibit complex and sometimes opposing functions in cancer biology. These enzymes can function as tumor suppressors or promoters, depending on the cellular context, tumor type, and metabolic state. This review provides a mechanistic overview of SIRT isoform regulation of key oncogenic processes, including proliferation, metastasis, metabolic reprogramming, and chemotherapy resistance. Special emphasis is given to their immunomodulatory roles within the tumor microenvironment (TME), where SIRTs influence T cell differentiation, immune checkpoint expression, macrophage polarization, and natural killer cell function. SIRT-driven pathways, such as the nicotinamide phosphoribosyltransferase (NAMPT)–SIRT1–programmed Cell Death Ligand 1 (PD-L1) axis, SIRT6-induced regulatory T cell (Treg) formation, and SIRT2-driven T cell activation, are examined for their effects on immune escape or enhancement and their impact on immunotherapy responses. The review also explores how SIRTs contribute to adaptive mechanisms underlying chemoresistance, including autophagy, epithelial-mesenchymal transition (EMT), redox balance, and mitochondrial protection. The therapeutic landscape of targeting SIRTs is assessed, with discussion of isoform-selective modulators, combination strategies with checkpoint blockade, and challenges in leveraging their context-dependent activities. SIRTs are established as crucial regulators of cancer immunity and therapy, suggesting novel directions for precision oncology. However, given their isoform- and context-dependent duality across tumor types, the clinical translation of SIRT modulators requires careful mechanistic stratification and biomarker-guided patient selection.